Efficacy and side effects of long-term treatment strategies of canine primary hypoadrenocorticism - Dobosz, Deborah Anna; Zablotski, Yury; Wehner, Astrid (Frontiers in Veterinary Science, 2026)
BackgroundHypoadrenocorticism (HA) with hyponatremia and hyperkalemia represents primary disease and indicates cortisol and aldosterone insufficiency. Treatment involves replacement of mineralocorticoids and glucocorticoids. There are currently no studies comparing the efficacy and side effects of different treatment protocols.ObjectivesThe aim of this study was to compare different treatment protocols for dogs with hyponatremic and hyperkalemic HA regarding their efficacy and side effects.AnimalsTwo hundred forty-four dogs with HA with electrolyte anomalies.MethodsData were collected via a standardized online questionnaire (available in english and german), which caregivers of affected dogs completed. The questionnaire was given to clients and was spread in online media.ResultsA total of 244 complete questionnaires were received (109 german and 135 english). Of those 244 participating dogs, 126 were female and 118 were male. Based on the treatment applied, the following groups were assigned: prednisolone and desoxycorticosterone pivalate (DOCP, Zycortal®) (ZP, n = 167), prednisolone and desoxycorticosterone pivalate (DOCP, Percorten-V®) (PP, n = 39), prednisolone and fludrocortisone (FP, n = 23) and fludrocortisone (F, n = 15). The median prednisolone dose was 0.07 mg/kg/day in the ZP and 0.08 mg/kg/day in the FP group and was slightly lower in the PP group with 0.04 mg/kg/day. Median DOCP dose was 0.88 mg/kg every 28 days in the ZP group and 0.78 mg/kg every 28 days in the PP group. Fludrocortisone was dosed with 0.02 mg/kg/day in the FP and F group. All treatment strategies led to a normal activity, quality of life of dog and caregiver, and achieved satisfaction with therapy.ConclusionGood clinical disease control can be achieved with any of the above strategies. Applied DOCP dose were lower than previously reported and can be combined safely with low prednisolone dosages.